2020
DOI: 10.1039/c9tb02101a
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle/sink model composed of β-cyclodextrin and simvastatin-loaded discoidal reconstituted high-density lipoprotein for enhanced cholesterol efflux and drug uptake in macrophage/foam cells

Abstract: The combination of β-CD and ST-d-rHDL could serve as a shuttle/sink model to enhance cholesterol efflux and drug uptake in macrophage/foam cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In this delivery system, simvastatin (ST) was selected as a model statin drug to suppress plaque inflammation and promote cholesterol efflux [ [31] , [32] , [33] ]. β-CD-anchored discoidal recombinant high-density lipoprotein (rHDL), termed as NP 3 ST , was utilized as a core as it was shown to possess not only deep plaque penetration property by virtue of its small size but also plaque targeting and cholesterol removal ability [ 34 , 35 ]. Fc was grafted onto hyaluronic acid (HA), and the resulting HA-Fc conjugates were utilized to crosslink NP 3 ST through multivalent host-guest interactions between β-CD/Fc to form ROS-responsive nanoassemblies (HA-Fc/NP 3 ST ) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this delivery system, simvastatin (ST) was selected as a model statin drug to suppress plaque inflammation and promote cholesterol efflux [ [31] , [32] , [33] ]. β-CD-anchored discoidal recombinant high-density lipoprotein (rHDL), termed as NP 3 ST , was utilized as a core as it was shown to possess not only deep plaque penetration property by virtue of its small size but also plaque targeting and cholesterol removal ability [ 34 , 35 ]. Fc was grafted onto hyaluronic acid (HA), and the resulting HA-Fc conjugates were utilized to crosslink NP 3 ST through multivalent host-guest interactions between β-CD/Fc to form ROS-responsive nanoassemblies (HA-Fc/NP 3 ST ) [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increased penetration of miNano due to the impaired endothelial barrier in atherosclerotic arteries may be another mechanism. We also observed that miNano co-localized well with macrophages within plaques, implying that phagocytosis by monocyte in the circulation followed by accumulation in the plaque may be another way for miNano to enter into plaques, though the latter is less likely since the relatively small diameter of miNano prevents it from phagocytosis [ 58 ]. Like most rHDLs [ 59 ], miNano is eliminated by the liver with limited elimination by the kidney, as shown by fluorescence signal accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of HP-β-CD can extract cholesterol from the cell membrane, especially from lipid rafts. At the same time, it can slightly decrease the levels of intracellular cholesterol; however, a high concentration of β-CD causes cholesterol accumulation in the ER [ 37 ]. Lipid rafts are mainly composed of sphingolipids and cholesterol.…”
Section: Discussionmentioning
confidence: 99%